The Construction Workers' Strike on the Canadian Pacific Railway, 1879 - Hall, David (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1995)
In May 1879 construction workers struck on contract 15 of the CPR to demand back pay, restoration of wage structures, and improved board and medical attendance. The working conditions, causes, and outcome of the strike were typical of the situation for unskilled labourers on large construction projects in the 19th century. The workers gained their back pay, but little else. At the same time, the strike contributed to the loss of the contract by the contractor, Joseph Whitehead, and perhaps also contributed to the end of the small contract system of building the transcontinental railway.